A Review Article on Aswagandha (Withania somnifera) – The Natural Immunity Booster - Sivan, Archana; Vani , Gayathri P A; Singh, Chandan; Purvia, Rajendra Prasad; Adlakha, Manoj (International Research Journal of Ayurveda & Yoga, 2022)
Introduction - Ayurveda a holistic system of medicine, originated in India more than 3000 yrs ago. The main objective of Ayurveda is to “Maintain the health of healthy person and to pacify the disease of a diseased person”. Immunity is the ability of the body to resist against the various foreign agents. The concept of immunity, in fact had been rooted in Ayurvedic system of medicine much before 600 BC. Material and Methods - In Ayurvedic classics Acharya’s has mentioned a lot of immune boosters, both single drugs and formulations. Ashwagandha, is one among them, which has got immense popularity recently, due to its ability to boost body immunity and also, it can increases body’s natural ability to fight viruses. Discussion- Ashwagandha, a special herb, used extensively in Ayurveda and is known for its capacity to boost the immunity. The pharmacodynamic action of Aswagandha itself proves the immunomodulatory effects. The herb is ushna in potency thereby reduces Kapha Vata, providing more strength to the immune system of our body. Being Madhura in rasa it provides ojas, bala and nourishment to the Dhatus. Conclusion- An effort to compile the details about Aswagandha in relation to its immune boosting power was done here.